An exponential model for dependent defaults - Kay Giesecke (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2002)
A thorough understanding of the joint default behavior of credit-risky securities is essential for credit risk measurement as well as the valuation of multi-name credit derivatives and Collateralized Debt Obligations. In this paper we study a simple and tractable intensity-based model for correlated defaults, in which unpredictable default arrival times are jointly exponentially distributed. Since all critical results are given in closedform, the model can be easily mplemented. The efficient simulation of dependent default times for pricing and risk management purposes is straightforward as well. Parameter calibration relies on readily available market data as well as data and figures provided by rating agencies and credit risk management solutions.
urn:nbn:de:kobv:11-10049100
Keywords: G12; G13; 330; simulation; correlated defaults; multivariate exponential model